KECEMASAN REMAJA DALAM MENGHADAPI MENARCHE - Wahdah, Rabia (Midwifery And Complementary Care, 2022)
Background: Adolescence is a period during which puberty occurs. During this time, physical changes take place, including the development of secondary sexual characteristics, the onset of fertility, and psychological changes. These changes typically occur between the ages of 9 to 15. Menarche is the first menstruation experienced by a girl, resulting from hormonal processes. Anxiety related to menarche refers to a state of emotional tension marked by physical unease, worry, and the anticipation that something negative may happen during this first menstrual experience. Objective: To explore adolescent anxiety in facing menarche. Method: This journal analysis was conducted through a literature search using Google Scholar and PubMed. Results: The findings indicate that adolescents experience anxiety when facing menarche. Keywords: Anxiety, Adolescents, Menarche